Buffalo Bill's America William Cody and the Wild West Show - Warren, Louis S. (A Borzoi book, 2005)
Explores the life and times of the colorful Pony Express rider, trapper, Civil War soldier, professional buffalo hunter, Indian fighter, cavalry scout, actor, and dime-novel hero within the social and cultural context of his era.